(untitled) (Kronika Bydgoska, 2010)
The year 2011 marked the 50th anniversary of the commencement of the construction of one of the most attractive cultural facilities in Bydgoszcz city - an opera theatre, which has become a professional musie institution named Opera Nova. The new facility was opened on October 21, 2006, though its construction was officially finished two years later, in January 2008. In the real cycle, this investment project took 414 months, i.e. 34 years and 5 months, which is a record in the construction of theatre buildings in post-war Poland. The history of the construction of the opera edifice in Bydgoszcz is recorded in about 1,000 archival files, kept in the new edifice of the Opera Nova. Eveiything started ffom the then director of the Pomeranian Philharmonic Andrzej Szwalbe, though the finał success of the construction stretched on is the result of the determination of individual people and teams, including opera directors, social activists, musie lovers, artists, politicians, office workers, and finally architects, engineers and builders. Thanks to them, the Opera Nova - the host of the facility functioning in its own, modem seat - is nowadays among the well-known and highly valued opera theatres in Poland and abroad.